EKSPLORASI VISUAL MENGGUNAKAN CAT AKRILIK PADA BARANG MODE BEKAS UNTUK PENGGUNAAN BERKELANJUTAN - Yogantari, Made Vairagya (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
Fast fashion is an industrial trend with the concept of shorten the time (production, distribution, etc.) and offering new products to the market as quickly as possible (Tsan-Ming Choi, 2013). Changes in trends so rapidly driven by big players in the fashion industry where they instill a dogma in the minds of consumers about the ideal fashionable appearance. The development of technology helps fashion goods advertising on social media more massive so that the decision to buy by consumers becomes faster. Seeing this phenomenon the author conducted an experiment that was applied to the color theory courses in the Fashion Design study program at the Bali College of Design (STD) which had two objectives. The first is to find out how the visual exploration process uses acrylic paint on used fashion items. The second is to observe the added value of used fashion items so that they can be used sustainably. This creative exploration experiment is conducted by referring to re-imagine in 5R (recycle, reuse, reduce, re-design, re-imagine) proposed by Esty and Winston (2009), where the added value given to fashion items is expected to provide more power in visual attraction so that the use of fashion items can be sustained.